Analisis Sistem Manajemen Kesehatan dan Keselamatan Kerja pada Departemen Fasilitas dan Sarana PT Industri Kapal Indonesia (Persero) Makassar - Aliefiah Maghfirah Rahman; Masita Alya Rahma; Putri Zhachilia Susanto; Djuanda Djuanda; Muhammad Agung (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
This study aims to determine the Management System and the effectiveness of the Occupational Health and Safety Management System for Employees of the Facilities and Facilities Department of PT Industri Kapal Indonesia (Persero) Makassar. This study uses a qualitative approach method with several data collection techniques, namely interviews, semi-structural, observation, and documentation. In this study, informants were selected according to the research criteria consisting of 1 K3LH Manager, 1 Supervisor, 1 Foreman, and 4 Employees of the Facilities and Facilities Department. Data collection was carried out at PT Industri Kapal Indonesia (Persero) Makassar. The method used to analyze the data is the data triangulation technique consisting of data reduction, data presentation, and drawing conclusions to ensure data reliability. The results of the study indicate that the implementation and level of effectiveness of the occupational health and safety management system are (a) determination of K3 policies with an average percentage of 78%; (b) K3 planning with an average percentage of 79%; (c) implementation of K3 plans with an average percentage of 80%; (d) monitoring and evaluation of K3 performance with an average percentage of 78%; (e) review and improvement of SMK3 performance with an average percentage of 78%, and (f) implementation of SMK3 with an average percentage of 75%. Based on this, the effectiveness of the occupational health and safety management system in reducing the number of work accidents for employees is quite good, as evidenced by efforts to achieve zero accidents.